From policy to practice: examining the impact and implementation of the rapid land release program in addressing South Africa's housing backlog - Meka, Kgothatso (Department of Construction Economics and Management, 2025)
This dissertation critically examines the Rapid Land Release Program (“RLRP”) as a policy intervention designed to address South Africa's persistent housing backlog. The RLRP, rooted in the principles of incremental housing, aims to provide serviced land to beneficiaries for self-construction, reflecting a shift from traditional, fully built housing approaches. This study evaluates the program's implementation, its alignment with national housing objectives, and its capacity to address housing inequalities effectively. Adopting a qualitative research approach, the study utilizes semi-structured interviews with policymakers, housing practitioners, and community leaders, complemented by document analysis of academic literature and relevant policy frameworks. The findings reveal both opportunities and challenges inherent in the RLRP. Key strengths include its potential to empower communities, reduce fiscal burdens, and promote sustainable housing delivery. However, the study identifies critical gaps in institutional capacity, policy clarity, and infrastructure delivery that hinder the program's success. The research highlights the need for strengthened intergovernmental coordination, enhanced community engagement, and robust monitoring and evaluation frameworks to address these challenges. Furthermore, the study emphasizes the importance of aligning the RLRP with broader housing policies to ensure it serves diverse population segments, including the very poor, who may be unable to benefit from incremental housing models. This dissertation contributes to the discourse on housing policy in South Africa by offering actionable recommendations to optimize the RLRP's implementation and align it with global best practices. The findings underscore the necessity for systemic reform and multi-stakeholder collaboration to realize the program's potential in addressing South Africa's complex housing needs.